Effects of onshore-offshore sediment movements on beach profiles - Çelikoglu, Y; Çevik, E; Yüksel, Y (A A BALKEMA PUBLISHERS, 2000)
Change of coastal morphology depends on incident wave conditions, beach slope and sediment characteristics. Onshore-offshore sediment transport rate exposed to waves is very important for coastal morphology for the short term variation of the coasts, because beach profile is formed by the transport of sediment. In this study, a series of experimental investigations were carried out for the determination of volumetric change of beach profiles under three different bed materials and two different beach slopes.
Keywords: onshore-offshore sediment transport; coastal morphology; wave; beach profile; EQUILIBRIUM; Engineering; Mathematics; Water Resources